‘Tak seorang pun ditinggalkan’: Tujuan pembangunan berkelanjutan dan urgensi asistensi sosial yang integratif bagi penyandang disabilitas - Madyaningrum, Monica Eviandaru; Wijayanto, Murti Hadi; Indrayanti, Maria Irenne (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2025)
This article describes the experiences of families from lower middle socio-economic levels who have children with multiple disabilities. The experiences of these families are then analyzed in relation to the concept of the Sustainable Development Goals (SDGs) to explore social intervention models and strategies that may promote a more just, inclusive, and sustainable society. This article was developed based on the researchers’ involvement in a support group for families from lower middle socio-economic levels who have children with multiple disabilities. In addition, this article was also specifically prepared based on the experiences of producing a participatory video making that involved four families in the support group being studied. Qualitative data which became the main data source for this article were obtained from several data collection processes that occurred during the production of the documentary video. The data collection processes included two focus group discussions and two semi-structured interviews with each family. The data were analysed by using thematic analysis techniques. The overall findings of this research are summarized in two major themes, namely